(3GdeMGSHI GdeGdjI (B2 :s (3OQhS hCeKdI h JeGQjf eMdhdI (B/s - (3eQhT, jhSa s ((3GdLRGFQ(B: s (3OGQ CLjGd GdQbej (B, s, 2023)
(3eMGSHI eQOhOGJ GdeTJQjGJ hGdeHjYGJ, eMGSHI GdJSHjbGJ Ydi GdeNRhfGJ , cPdc eMGSHI GdJNajVGJ GdJLGQjI hGdeGdjI, heMGSHI GdCZdaI hGdChQGb GdJLGQjI, eY OQGSI MSGHGJ GdJSjjQ(B-(3GdCYHGA hGdefJhLGJ(B- (3CYeGd fgGjI GdOhQI(B.s
(3eQGLY U(B.277s
Keywords: (3GdChQGb GdJLGQjIs; (3GdeMGSHI GdJMdjdjIs